Deteksi Dini Pencegahan Penyalahgunaan NAPZA Pada Siswa Sekolah Menengah Kejuruan - Anwarudin, Anwarudin; Astuti, Dian Wuri; Unika, Maria; Prayoga, Aldi; Laim, Jois G.; Maximilianus, Maximilianus; Aini, Amalika Sifa; Katarina, Shinta (Jurnal Abdimas Jatibara, 2024)
Adolescence is a transition period between childhood and adulthood, which begins when sexual maturity occurs between the ages of 11 or 12 to 20 years. Adolescence is very vulnerable to cases of NAPZA abuse, where currently the case has entered the critical stage. Therefore, it is necessary to take preventive measures in the form of education. The aim of this community service is to increase the knowledge of teenagers (vocational school students) about the dangers of drug abuse for health as well as screening for methamphetamine abuse. The methods used include situation analysis through field surveys, education, and methamphetamine screening examinations. The results obtained were in the form of increased knowledge, understanding and awareness of the dangers of drug abuse as well as negative methamphetamine screening results for class X students at SMK Giri Handayani Gunungkidul DIY.